2020
DOI: 10.1007/s10585-020-10056-w
|View full text |Cite
|
Sign up to set email alerts
|

Is repeated pulmonary metastasectomy justified?

Abstract: Recurrence after pulmonary metastasectomy (PM) is frequent, but it is unclear to whom repeated pulmonary metastasectomy (RPM) offers highest benefits. Retrospective analysis of oncological and post-operative outcomes of consecutive patients who underwent PM from 2003 to 2018. Overall survival (OS) and disease-free interval (DFI) were calculated. Cox regression was used to identify variables influencing OS and DFI. In total, 264 patients (female/male: 114/150; median age: 62 years) underwent PM for colorectal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 30 publications
(71 reference statements)
0
17
0
Order By: Relevance
“…However, only 20% of these patients would be treated with RPM. 4,[14][15][16][17][18][19] In our study, 64 patients after PM, 78% of the initial study population were identified with a tumor relapse in the follow-up. Only 26 patients of This document was downloaded for personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…However, only 20% of these patients would be treated with RPM. 4,[14][15][16][17][18][19] In our study, 64 patients after PM, 78% of the initial study population were identified with a tumor relapse in the follow-up. Only 26 patients of This document was downloaded for personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…Stage 3 (Orange) represents an intermediate group where a cautious indication may exist [ 18 , 19 ]. Although preliminary successful validation has been reported at the meeting on a retrospective cohort of 264 patients, this approach is being validated in a larger group of patients [ 20 ].…”
Section: Group 81mentioning
confidence: 99%
“…The phenomenon has been observed in at least four of the observational studies in the list of references in the paper by Dr Forster and colleagues. (1) We addressed the matter in an Editorial in the Journal of Thoracic and Cardiovascular Surgery five years ago, using data from the work of the late Professor Mineo(2) and we have reconsidered the conundrum in the light of this new study. (1) The first place to look for a possible explanation is in the Kaplan-Meier curves in Fig.…”
Section: Is Survival Really Better After Repeated Metastasectomy?mentioning
confidence: 99%
“…(1) We addressed the matter in an Editorial in the Journal of Thoracic and Cardiovascular Surgery five years ago, using data from the work of the late Professor Mineo(2) and we have reconsidered the conundrum in the light of this new study. (1) The first place to look for a possible explanation is in the Kaplan-Meier curves in Fig. 1 because that is the most readily grasped presentation of the data and contains the time to death of all 246 patients.…”
Section: Is Survival Really Better After Repeated Metastasectomy?mentioning
confidence: 99%